PERFORMANCE ANALYSIS OF WATERMARKING APPROACH FOR VLSI DESIGN INTELLECTUAL PROPERTY PROTECTION - MEENAKUMARI, M. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
VLSI technology brought revolution in EDA industry. Fabrication of complicated system on a chip is possible by using reusable module called Intellectual Property (IP) core. IP cores that became an integral part of the electronic design industry influenced and had a rather significant and almost incomparable impact with respect to system designing in any chip. IP designs for any organization are imperative; contrary, IP designs that are shared can significantly cause high security risks. The majority of IP’s require time as well as effort for purposes of designing and verification, however there still remains the possibility of these being copied or minor modifications to hide proof of ownership. To overcome this problem watermarking technique is recommended for IP Core protection. Watermark insertion in multilevel increases the security of the system. In this paper the ownership information is inserted in state transition outputs of State Transition Graph employing hierarchical representation of Finite state Machine (FSM) and subsequently in the netlist level by embedding watermark in the delay between the states. Watermark insertion at two levels increases the security of the design. Signature generation uses cryptographic algorithm for enhancing the security of the IP core designs. The experimental results show that performance is improved.